2005
DOI: 10.1002/adv.20050
|View full text |Cite
|
Sign up to set email alerts
|

PP/EVA blends: Mechanical properties and morphology. Effect of compatibilizers on the impact behavior

Abstract: ABSTRACT:The mechanical properties of blends of isotactic polypropylene (PP) and poly[ethylene-co-(vinyl acetate)] (EVA) are studied under tension at several temperatures (from -30• C to room temperature). The morphology and thermal properties are given attention at every stage of the stretching process. To improve the impact resistance of the blends, poly[propylene-graft-(maleic anhydride)] (PPMA) and hydroxylated EVA (EVAOH) are used as compatibilizers. The domain size of the dispersed phase decreases with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 38 publications
(27 reference statements)
8
30
0
Order By: Relevance
“…This better dispersed morphology could be attributed to the interfacial interactions and to the effectiveness of the shear mixing exerted by the screw configuration used. Similar results were obtained by Maciel et al,13 who found a reduction in particle size of the dispersed EVA phase when a compatibilizer was incorporated to the blend. These smaller an better dispersed domains confirms the higher interaction of the PP‐ r ‐EP, even at lower EVA content of the blends, previously demonstrated by a single and unique T g (E“) and by the melting temperature depression observed by DSC.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This better dispersed morphology could be attributed to the interfacial interactions and to the effectiveness of the shear mixing exerted by the screw configuration used. Similar results were obtained by Maciel et al,13 who found a reduction in particle size of the dispersed EVA phase when a compatibilizer was incorporated to the blend. These smaller an better dispersed domains confirms the higher interaction of the PP‐ r ‐EP, even at lower EVA content of the blends, previously demonstrated by a single and unique T g (E“) and by the melting temperature depression observed by DSC.…”
Section: Resultssupporting
confidence: 89%
“…6). This mechanical property behavior was also observed by Ramirez‐Vargas et al12 and Gupta et al7 Maciel et al13 has reported an increase on the impact strength in PP/EVA blends when using PPMA and EVAOH as compatibilizers.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In content of 40 % of EVA in the blend, the impact resistance increased of more than 270 % with the addition of 6.2 phr of compatibilizers at ambient temperature. Moreover, with increasing the compatibilizer content to 10 phr, an additional rise in the impact resistance was obtained [3].…”
Section: Introductionmentioning
confidence: 99%